ECOLOGICAL CULTURE AND ITS FORMATION (Proceedings of International Conference on Modern Science and Scientific Studies, 2022)
In the first phase of the development of ecological culture,  attitudes  toward nature in secondary schools, To assist individuals desiring to   benefit the worldwide   work  of Jehovah's Witnesses through   some form  of charitable giving, a  brochure entitled Charitable Planning to Benefit    Kingdom  Service Worldwide has been prepared.